What Are the Multi-Omics Mechanisms for Adaptation by Microorganisms to High Alkalinity? A Transcriptomic and Proteomic Study of a Bacillus Strain with Industrial Potential - SAYAR, AHMET ALP; SARIYAR AKBULUT, BERNA; KAZAN, DİLEK; ALTINIŞIK KAYA, FATMA ECE; SAYAR, NİHAT ALPAGU (MARY ANN LIEBERT, INC, 2018)
Alkaliphilic organisms are among an industrially important class of extremophile microorganisms with the ability to thrive at pH 10-11.5. Microorganisms that exhibit alkaliphilic characteristics are sources of alkali-tolerant enzymes such as proteases, starch degrading enzymes, cellulases, and metabolites such as antibiotics, enzyme inhibitors, siderophores, organic acids, and cholic acid derivatives, which have found various applications in industry for human and environmental health. Yet, multi-omics mechanisms governing adaptation to high alkalinity have been poorly studied. We undertook the present work to understand, as a case study, the alkaliphilic adaptation strategy of the novel microorganism, Bacillus marmarensis DSM 21297, to alkaline conditions using a multi-omics approach that employed transcriptomics and proteomics. As alkalinity increased, bacteria remodeled the peptidoglycan layer by changing peptide moieties along with the peptidoglycan constituents and altered the cell membrane to reduce lipid motility and proton leakiness to adjust intracellular pH. Different transporters also contributed to the maintenance of this pH homeostasis. However, unlike in most well-known alkaliphiles, not only sodium ions but also potassium ions were involved in this process. Interestingly, increased pH has triggered the expression of neither general stress proteins nor gene encoding proteins associated with heat, salt, and nutrient stresses. Only an increase in the expression of oxidative stress related genes was evident. Endospore formation, also a phenomenon closely linked to stress, was unclear. This questioned if high pH was a real stress for B. marmarensis. These new findings, corroborated using the multi-omics approach of the present case study, broaden the knowledge on the mechanisms of alkaliphilic adaptation and might also potentially offer useful departure points for further industrial applications with other microorganisms.
Keywords: Bacillus marmarensis; alkaliphilic adaptation; transcriptomics; proteomics; multi-omics; systems and industrial biology; ALKYL HYDROPEROXIDE REDUCTASE; MECHANOSENSITIVE CHANNELS; ALKALIPHILIC BACILLUS; NA+/H+ ANTIPORTER; PROTON; PROTECTION; BACTERIUM; PROTEINS; FAMILIES; SUBTILIS